Information Systems, E-learning, and Knowledge Management Research 4th World Summit on the Knowledge Society, WSKS 2011, Mykonos, Greece, September 21-23, 2011. Revised Selected Papers - Lytras, Miltiadis D.; Ruan, Da.; Tennyson, Robert D.; Ordonez De Pablos, Patricia.; Garca̕ Peąlvo, Francisco Jos.̌; Rusu, Lazar. (Communications in Computer and Information Science,, 2013)
This book constitutes the proceedings of the 4th World Summit on the Knowledge Society, WSKS 2011, held in Mykonos, Greece, in September 2011. The 90 revised full papers presented were carefully reviewed and selected from 198 submissions. The papers address issues such as information technology, e-learning, e-business, cultural heritage, e-government.